1998
DOI: 10.1088/0031-8949/57/5/002
|View full text |Cite
|
Sign up to set email alerts
|

R-matrix Calculation of C III Bound and Continuum Fine-structure States

Abstract: An approach to atomic structure calculations is described, using recent developments in the pseudo-state/R-matrix method, within the high optimization offered by close-coupling. These include the exploitation of the “QB” method for systematic resonance analysis, the definition and use of “core base states” for the target, and the incorporation of relativistic effects in the Opacity Project codes. A comprehensive set of data is calculated for fine-structure bound and continuum states of the form 1s22snl and 1s2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 21 publications
2
13
0
Order By: Relevance
“…) agrees quite well with the measured value [29] as well as with other calculations [36,37,39,41,42].…”
Section: Energies and Oscillator Strengths Of C Iiisupporting
confidence: 91%
See 2 more Smart Citations
“…) agrees quite well with the measured value [29] as well as with other calculations [36,37,39,41,42].…”
Section: Energies and Oscillator Strengths Of C Iiisupporting
confidence: 91%
“…) agrees within the uncertainty of the measured value by Kwong et al [34] and with the result from Berrington et al [39], while that from Froese Fisher et al [36,37] agrees almost exactly with the measured value by Doerfert et al [35]. Froese Fischer et al [36,37] included the Breit interaction in an indirect manner and found the effect to be important for the intercombination transitions.…”
Section: Energies and Oscillator Strengths Of C Iiisupporting
confidence: 86%
See 1 more Smart Citation
“…Recently, several relativistic calculations of transition probabilities have been carried out using the Breit-Pauli R-matrix method (BPRM); e.g. for Fe XXV and Fe XXIV (Nahar & Pradhan 1999), C III (Berrington et al 1998), Fe XXIII (Ramírez et al 2000). These calculations produced highly accurate oscillator strengths for most transitions considered, within a few percent of experimental data or other accurate theoretical calculations (where available).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison between calculated width, G a , in meV units (meV), belonging to 1s 2 2pns( 1 P 0 ) autoionizing states, 5 n 12, in C 3þ . Results refer to the R-matrix Floquet theory and code and its extension to LIDS method, and the R-matrix calculation by Berrington et al (1998) In atomic or molecular physics, it is customary the use of sum rules to handle the matrix elements that appear in many computations (Biedenharn & Rose, 1953;Biedenharn, 1955). These formulae are particularly well suited for the study of autoionization of large-angular momentum doubly excited Rydberg states.…”
Section: First-order Perturbative Calculation In a Single-configuratimentioning
confidence: 99%